The Challenges of Data Comparison and Varied European Concepts of Diversity - Katherine Marquand Forsyth; Vanja M. K. Stenius (Fondazione Eni Enrico Mattei (FEEM), 2006)
Immigration to Germany, Italy and Finland represent different stages of the new migration to Europe. The scale and types of immigration also differ between the three. Though each country is experiencing different stages of immigration, they all recognize the necessity to better integrate foreign minors. The three countries seem to have only recently started to regard themselves as countries of immigration. As a result, their policies towards foreign minors seem to be based on tolerating, not integrating them. The presence of foreign minors in the juvenile justice system is a reflection on their approaches and attitudes towards immigrants. Therefore, we set out on an 18-month project funded by the European Commission to study how being foreign affects the treatment of minors in the penal systems in Italy, Germany and Finland. The project is called INTO: Inside the Outsiders: Deviant Immigrant Minors and Integration Strategies in European Justice Systems. In this paper, we will present the difficulties encountered when creating comparable data in terms of contrasting labels for and definitions of the target group and data collection as well as the solutions created for addressing these difficulties. At the outset of the project, it became clear that the terms used to define the target group had different meanings for each of the partners and one term was not deemed sufficient for use in all three contexts, both due to the immigration history in each country and due to the counting methods used by the data collection institutions in each country (National Censuses, Justice Systems, etc.). In the project proposal, we defined immigrant minors as including two categories of children: 1) those born in the host country and are either naturalised citizens, hold dual citizenship or are permanent residents 2) children who immigrated to the host country with their family or by themselves. Yet statistical data in each country uses multiple and diverse terms to describe our target group foreign minors, migrants, ethnic minorities, foreign citizens, etc. Clearly, this made the collection and comparison of three different sets of national statistics quite challenging. The diverse terminology and categorisation of immigrant minors in the three countries made it difficult to find directly comparable statistics. The discussion of how to resolve this technical difficultly revealed the different conceptions of what it means to be an immigrant and a minor in each country and within their respective social and judicial systems. This discussion reflected each countrys individual conceptions and laws regarding citizenship as well as their past and present approaches to integration. We argue that despite their different labels, social class and rights, foreigners, ethnic minorities and migrants share similar social conditions. Foreigners, even when they become citizens, still experience social constraints and suffer in the process of cultural integration. Migrants, who must overcome the legal and economic challenges and risks of migrating, have difficulty fully integrating into the host society. The second generation seems to experience greater frustration from their continued exclusion. Ethnic minorities are often identifiable and visibly different from the majority which prevents their full integration despite being long-established in a country. They all remain foreign from the perspective of the autochthonous population. And when examining discrimination, we find that these terms often overlap and are used interchangeably. Given this background, it is no wonder that there are difficulties in addressing this new migration to Europe. The social conflicts arising from the recent migration, during the last fifty years (at most), cannot be easily understood in terms of class, racial or ethnic conflict. While we might say the subjects of this conflict belong to a socially disadvantaged group or that our societies are quick to discriminate against them, we cannot, since the situation is still not clear. What is clear is that it will continue to be difficult to study these difficult issues in a European setting if we lack of adequate, comparable data collection techniques in Europe. However, refining the techniques will require serious reflection and discussion of the terms currently in use and of the theoretical approaches to immigration in each of the European member states. This is a reflection we intend to begin in this paper.
Keywords: 330; Diversity; Immigrant Minors; Marginalisation; Criminality